Peran Hukum Bisnis dalam Menjamin Perlindungan Bagi Eksportir, Importir, dan Investor Pada Perdagangan Internasional di Era Globalisasi - Ferren Chaniago (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2026)
This study examines the role of business law in ensuring protection for exporters, importers, and investors in international trade amid globalization. The research addresses two key issues: the effectiveness of dispute resolution mechanisms (national law, international courts, and arbitration) and the role of business law in regulating legal protections, particularly for international payment methods. The normative juridical method was employed, analyzing primary and secondary legal materials, including Law No. 7/2014 on Trade, Law No. 30/1999 on Arbitration, and Bank Indonesia Regulation No. 20/2018. The findings reveal that national law is effective for simple disputes but limited in cross-border enforcement. International arbitration proves more efficient, though challenges such as costs and low awareness among businesses persist. Additionally, the study highlights regulatory gaps in addressing globalization challenges, such as digital trade and cSurrency fluctuations. The research concludes that revising national legal frameworks, enhancing outreach programs, and harmonizing with international standards are critical to strengthening legal protections for businesses.